Evaluation of pharmacological activities and active components in Tremella aurantialba by instrumental and virtual analyses - Yan, Yonghuan; Wang, Mengtian; Gan, Xiaoruo; Wang, Xu; Fu, Chenghao; Li, Yuemin; Chen, Ning; Lv, Pin; Zhang, Yan (Frontiers in Nutrition, 2022)
As a kind of medicinal and edible homologous fungus, there is a lack of data on the medicinal value of Tremella aurantialba. In this study, 135 chemical components were identified in Tremella aurantialba by UPLC-Q-TOF/MS. Moreover, the bioactivity of Tremella aurantialba was found in five diseases and potential therapeutic targets were revealed using network pharmacology. Finally, the significant neuroprotective, anticancer, immune, hypoglycemic and cardiovascular effects of Tremella aurantialba and 14 related key active compounds were proposed. The existence of these bioactive natural products in Tremella aurantialba is consistent with the traditional use of Tremella aurantialba. More importantly, the comorbidity molecular mechanisms and therapeutic targets of five diseases were explored. This study is the first to systematically identified chemical components in Tremella aurantialba and successfully predicted its bioactivity, key active compounds and drug targets, providing a reliable novel strategy for future research on the bioactivity development and utilization of Tremella aurantialba.